RELIABILITY AND VALIDITY OF MAXILLARY AND SPHENOID SINUS MORPHOLOGICAL VARIATIONS IN THE ASSESSMENT OF SKELETAL MATURITY - Mahmood, Hafiz Taha; Shaikh, Attiya; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2018)
Background: The present study aimed at assessing the relationship between growth changes in maxillary (MS) and sphenoid sinus (SS) and cervical vertebral maturation (CVM) and to evaluate their reliability and validity in assessing the skeletal maturity of an individual. Methods: A cross-sectional study was conducted on the pretreatment lateral cephalograms of 224 patients (males=116, females=108) aged 8-17 years. MS and SS heights, widths and indices were evaluated. The subjects were classified according to six stages based on CVM using Baccetti's method. Kruskal-Wallis test was applied to compare MS and SS measurements at different cervical stages for each gender. Kappa statistics, positive predictive value, negative predictive value, sensitivity and specificity were calculated to test the diagnostic accuracy of MS and SS indices. Results: The MS and SS indices varied significantly (p<0.001) at different cervical stages for both gender. Kappa statistics showed significant agreement using MS (p<0.001) and SS indices (p<0.05). The diagnostic performance of MS index (Sensitivity ‰¥71%) was found to be better than SS index (Sensitivity ‰¥65%). Conclusions: The MS height, width and index in both genders and SS height, width and index in males and only SS width and index in females were significantly associated with the CVM stages. The validity of MS and SS indices were comparable for females; whereas, the MS index offers significant advantage over SS index for the assessment of growth status of males. Keywords: Maxillary Sinus; Sphenoid Sinus; Cervical Vertebral Maturation